(untitled) (Islamic Sciences Journal, 2023)
Praise be to Allah, Lord of the Worlds, and blessings and peace be upon the Master of the Messengers, our Master Muhammad, and upon all his family and companions: As for after: This research entitled: (The Suspicion of Inheritance and the responses of Muhammad Amara, "may Allah have Mercy on him") included Muhammad Amara’s response to the suspicion of inheritance raised by the secularists and those influenced by the West, through his statement of the wisdom of Islam in making the inheritance of a woman half of the inheritance of a man, inferred to that with texts from the Holy Quran and the Sunnah , He is following , the moderate approach in responding to the violators. Muhammad Emara - may God have mercy on him - went through many intellectual transformations: the Azhar stage, where he began his culture with the Holy Qur’an and based his vision on religious science, then joined some Egyptian leftist organizations, which is a phase of openness to the Western thought and the Marxist benefited him a lot and made him distinct among the persons of his generation, He saw the greatness of Islam in the light of the other, and he saw the size of the other in the light of Islam, Then he moved to the stage of equilibrium, which starts from the end of the second half of the sixties until the end of the seventies.